Crashing the party taking on the corporate government in an age of surrender - Nader, Ralph 1934- (Thomas Dunne Books/St. Martin's Press, 2002)
A behind-the-scenes glimpse into the presidential campaign of one of America's most effective social critics details what it takes to fight the two-party juggernaut.